Brain imaging and fluid biomarker analysis in young adults at genetic risk for autosomal dominant Alzheimer's disease in the presenilin 1 E280A kindred: a case-control study - Reiman, Eric M; Quiroz, Yakeel T; Fleisher, Adam S; Chen, Kewei; Velez-Pardo, Carlos; Jimenez-Del-Rio, Marlene; Fagan, Anne M; Shah, Aarti R; Alvarez, Sergio; Arbelaez, Andrés; Giraldo, Margarita; Acosta-Baena, Natalia; et al. (Lancet neurology, 2012)
We have previously characterised functional brain abnormalities in young adults at genetic risk for late-onset Alzheimer's disease. To gain further knowledge on the preclinical phase of Alzheimer's disease, we sought to characterise structural and functional MRI, CSF, and plasma biomarkers in a cohort of young adults carrying a high-penetrance autosomal dominant mutation that causes early-onset Alzheimer's disease. Between January and August, 2010, 18–26-year-old presenilin 1 (PSEN1) E280A mutation carriers and non-carriers from the Colombian Alzheimer's Prevention Initiative Registry in Medellín Antioquia, Colombia, had structural MRI, functional MRI during associative memory encoding and novel viewing and control tasks, and cognitive assessments. Consenting participants also had lumbar punctures and venepunctures. Outcome measures were task-dependent hippocampal or parahippocampal activations and precuneus or posterior cingulate deactivations, regional grey matter reductions, CSF Aβ1–42, total tau and phospho-tau181 concentrations, and plasma Aβ1–42 concentrations and Aβ1–42:Aβ1–40 ratios. Structural and functional MRI data were compared using automated brain mapping algorithms and search regions related to Alzheimer's disease. Cognitive and fluid biomarkers were compared using Mann-Whitney tests. 44 participants were included: 20 PSEN1 E280A mutation carriers and 24 non-carriers. The carrier and non-carrier groups did not differ significantly in their dementia ratings, neuropsychological test scores, or proportion of apolipoprotein E (APOE) ɛ4 carriers. Compared with non-carriers, carriers had greater right hippocampal and parahippocampal activation (p=0·001 and p<0·014, respectively, after correction for multiple comparisons), less precuneus and posterior cingulate deactivation (all p<0·010 after correction), and less grey matter in several parietal regions (all p<0·002 uncorrected and corrected p=0·009 in the right parietal search region). In the 20 participants (ten PSEN1 E280A mutation carriers and ten non-carriers) who had lumbar punctures and venepunctures, mutation carriers had higher CSF Aβ1–42 concentrations (p=0·008) and plasma Aβ1–42 concentrations (p=0·01) than non-carriers. Young adults at genetic risk for autosomal dominant Alzheimer's disease have functional and structural MRI findings and CSF and plasma biomarker findings consistent with Aβ1–42 overproduction. Although the extent to which the underlying brain changes are either neurodegenerative or developmental remain to be determined, this study shows the earliest known biomarker changes in cognitively normal people at genetic risk for autosomal dominant Alzheimer's disease. Banner Alzheimer's Foundation, Nomis Foundation, Anonymous Foundation, Forget Me Not Initiative, Boston University Department of Psychology, Colciencias, National Institute on Aging, National Institute of Neurological Disorders and Stroke, and the State of Arizona.